Characterisation of range restriction amongst the rare flora of Banded Ironstone Formation ranges in semiarid south-western Australia - Robinson, Todd; Virgilio, G.; Temple-Smith, D.; Hesford, J.; Wardell-Johnson, Grant (C S I R O Publishing, 2018)
Banded Ironstone Formation (BIF) ranges feature numerous rare and endemic plant species. We tested whether non-occurrence in neighbouring ranges is due to habitat dissimilarity across five groups of proximal ranges for three sets of species (18 taxa). Set 1 comprised 15 BIF-specialist species centred on the Helena and Aurora Range (HAR); Set 2, of one BIF species endemic to Mt Jackson and Set 3, of two non-BIF species. All species were used as input into ecological niche models to determine the importance and behaviour of five environmental variables derived from 2m resolution LiDAR imagery over 1605 km2, extrapolate habitat suitability and compare niche similarity. We hypothesised that if BIF species are not range-restricted, suitable habitat will be found on all five groups and variable importance and behaviour will be similar for Sets 1 and 2 but not for Set 3. Topographical control on surface hydrology is the most important predictive variable for most BIF species, with ruggedness and shade also important to species in Sets 1–2 but not Set 3, which either preferred flat plains or had no preference (habitat generalist). We conclude that habitat suitability is not range restrictive. Such endemism is more likely a result of stochasticity and limited seed dispersal.